Future reduction of cutaneous malignant melanoma due to improved sun protection habits and decreased common melanocytic nevi density among Swedish children?: A follow-up from 2002 to 2012. (September 2019) - Rodvall, Ylva; Wahlgren, Carl-Fredrik; Wiklund, Kerstin
Abstract: We have previously demonstrated significant improvements in sun protection regimens and significantly fewer common melanocytic nevi (CMN) among 7-year-old children in southern Sweden when comparing year 2007 with 2002. The aim of this study was to investigate whether the observed decreasing trend also can be observed at age 10 and, in addition, to compare the CMN density change between 7 and 10 years of age during two periods of time. Two open cohorts were used, cohort I with schoolchildren investigated in 2002 at age 7 and in 2005 at age 10 and cohort II with schoolchildren investigated in 2009 at age 7 and in 2012 at age 10. A significant decrease in CMN density (number/m 2 BSA) at age 10 from 2005 to 2012 was observed: 15.9 (14.7–17.2) and 11.4 (10.1–12.7), respectively. The density growth rate from 7 to 10 years was 2.8 (2.1–3.5) between 2002 and 2005 and decreased significantly to 0.9 (0.2–1.5) between 2009 and 2012. Significant increases were observed for 'often use of sunscreen', 'often staying in shade' and 'often staying indoors' from cohort I to cohort II: 65 vs 80%, 7.6 vs 13% and 7.3 vs 19%, respectively. The decrease in number of CMN among 10-year-old children confirms a current trend in Sweden. If this persists, a future reduction of cutaneous malignant melanoma incidence in Sweden might be anticipated. The results also indicate that CMN count could be used as an indicator of ultraviolet exposure. Highlights: Significantly improved sun protection among Swedish children between 2002 and 2012. The trend of decreased common melanocytic nevus density remains. Count of common melanocytic nevi can be used as indicator of past ultraviolet exposure. Reduced UV exposure among children is probably effective as melanoma prevention.